Physical and Mechanical Properties of Manglietla Sp. From Assam - Sanyal, S. N.; Rawat, N. S. (Indian Forester, 1981)
The physical and mechanical properties of Manglietia sp. Received from Margherita Range, Digboi Division, Assam and tested in Green and air-dry condition have been reported and the results have been compared with Manglietiainsignis and standard teak. Based on the strength figure obtained, its suitability indices for Industrial and Engineering uses and Safe working stresses have also been reported and possible end uses suggested.